1995 ЖЫЛҒЫ РЕСЕЙ МЕН БЕЛАРУСЬ АРАСЫНДАҒЫ КЕДЕН ОДАҒЫ ТУРАЛЫ КЕЛІСІМНІҢ НЕГІЗГІ ЕРЕЖЕЛЕРІ (Journal of actual problems of jurisprudence, 2019)
In the article the author deal with main statements of Agreement of Custom union 6.01.1995, wich was concluded betweenRussia and Belorussia, also it’s pays attention to some legal specialities of this treaty.